Social function of the state in modern society (Journal of Economic Research & Business Administration, 2015)
Article is devoted to questions of change of a role and function of the state, growth of its importance in all spheres of public and economic activity. Release of the state from superfluous administrative and allowing functions will allow it to concentrate resources on the solution of strategic tasks. Specifics of economic and social development of the states of the CIS demands a choice of special, Euroasian anti-recessionary and modernization strategy.
Keywords: Social economy; social policy of the state; social market economy; social justice; socialization of the public relations.